Designing a smart home model using EasyVR and Arduino for voice control of devices - Soufiane hachani (ITEGAM-JETIA)
This paper presents the design and implementation of a smart home model using easyVR and Arduino to voice control home appliances, without relying on traditional sensors. The system leverages easyVR, a voice recognition module, to process spoken commands, which are then interpreted by Arduino to control various smart devices, such as lights, TVs, and air conditioners. The proposed system aims to provide an affordable and efficient solution for home automation, offering a user-friendly, hands-free interface for users. The paper identifies the hardware and software components of the system, including the integration of easyVR with Arduino, and addresses the challenges of implementing accurate voice recognition in a real-world environment. A prototype is developed to demonstrate the functionality and effectiveness of the voice control system. The results show that the system responds reliably to voice commands, providing a seamless smart home experience. This paper demonstrates the potential of easyVR and Arduino in creating scalable and cost-effective voice-controlled smart homes.